2021
DOI: 10.7717/peerj.11215
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence of the avocado defense response to Fusarium kuroshium infection: a deep transcriptome analysis using RNA-Seq

Abstract: Fusarium kuroshium is a novel member of the Ambrosia Fusarium Clade (AFC) that has been recognized as one of the symbionts of the invasive Kuroshio shot hole borer, an Asian ambrosia beetle. This complex is considered the causal agent of Fusarium dieback, a disease that has severely threatened natural forests, landscape trees, and avocado orchards in the last 8 years. Despite the interest in this species, the molecular responses of both the host and F. kuroshium during the infection process and disease establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 150 publications
1
11
0
Order By: Relevance
“…BLASTp analysis was performed on the entire set of P. americana protein sequences and no additional PaNLR sequences could be identified. Furthermore, an independent study found only one TNL gene being expressed in Hass avocado stems during F. kuroshium infection ( Pérez-Torres et al, 2021 ). This validated that no TNL motifs were missed during PaNLR identification using the RGAugury program and WI genome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BLASTp analysis was performed on the entire set of P. americana protein sequences and no additional PaNLR sequences could be identified. Furthermore, an independent study found only one TNL gene being expressed in Hass avocado stems during F. kuroshium infection ( Pérez-Torres et al, 2021 ). This validated that no TNL motifs were missed during PaNLR identification using the RGAugury program and WI genome.…”
Section: Discussionmentioning
confidence: 99%
“…To date, 49 complete putative NLR genes have been identified in avocado using microarray and RNA-sequencing analysis ( Van den Berg et al, 2018 ; Pérez-Torres et al, 2021 ). In the study done by Pérez-Torres et al (2021) , Hass avocado stems were infected with Fusarium kuroshium , which causes Fusarium dieback disease in avocado. However, only four NLR genes were differentially expressed after F. kuroshium infection.…”
Section: Introductionmentioning
confidence: 99%
“…A PR-10 of the MLP (major latex protein) type was also identified, negatively regulating plant defense, and two other MLPs that were repressed in plants subjected to biotic stressors ( Wang et al., 2017 ; He et al., 2020 ; Pérez-Torres et al., 2021 ). Two fungal pathogens inhibited MLP expression.…”
Section: Discussionmentioning
confidence: 99%
“…Significant downregulation of an MLP-like 423 gene was observed during avocado defense response to Fusarium kuroshium infection as well as during apple infections with Botryosphaeria berengeriana f. sp. piricola and Alternaria alternata apple pathotype 58 , 59 . Moreover, apple calli overexpressing an MLP-like 423 gene had lower expression of resistance-related genes, and were more sensitive to fungal infections 59 .…”
Section: Discussionmentioning
confidence: 99%